Gynaecological pathology in women with Fowler's syndrome. (November 2015) - Karmarkar, Roopali; Abtahi, Bahareh; Saber-Khalaf, Mohammed; Gonzales, Gwen; Elneil, Sohier
Abstract: Objectives: To assess the prevalence of gynaecological pathologies in women with Fowler's syndrome (FS) which is characterised by chronic urinary retention (CUR) secondary to failure of urethral sphincter to relax and allow normal voiding. Study design: This was a case control study conducted at a tertiary referral centre specialised in managing women with FS. There were 41 patients with FS in the study group with CUR without mechanical obstruction of the urethra or neurological problem. All patients had raised maximum urethral closure pressure on urethral pressure profile, high urethral sphincter volume on ultrasound and complex repetitive discharges on eletromyography of the urethral sphincter. Normal voiding was established in these women after treatment with sacral neuromodulation. Fifty women without voiding dysfunction acted as control group. Data was obtained by using standard questionnaire for both the groups. Information was collected regarding gynaecological pathologies such as endometriosis, polycystic ovarian syndrome, menstrual abnormalities, ovarian cysts and subfertility and also regarding previous pregnancies. Analysis was performed using SPSS software from IBM Corporation. Results: At least one gynaecological pathology was present in 33 (80%) patients with FS compared to 16 (32%) women from control group ( P < 0.001). This included a higher incidence of endometriosis (29% versus 6%, P = 0.003), PCOS (24% versus 8%, P = 0.041) and subfertility (34% versus 8%, P = 0.003). The incidence of menstrual abnormalities and ovarian cysts was similar in both groups ( P > 0.05). Conclusion: Subfertility was more prevalent in women with FS in our study. Though the prevalence of different pathologies was higher in the FS group compared to the control group, it remained similar to that found in the normal female population in the published literature. Thus, it is not possible to state whether FS is caused by a hormonally based disorder. It took patients many years before they could get right diagnosis and treatment for FS. Early investigation of chronic urinary retention and referral to specialists for appropriate treatment in this small group of women can result in better health and improvement in their quality of life.